2014
DOI: 10.1063/1.4897544
|View full text |Cite
|
Sign up to set email alerts
|

Spin Hall magnetoresistance at Pt/CoFe2O4 interfaces and texture effects

Abstract: We report magnetoresistance measurements on thin Pt bars grown on epitaxial (001) and (111) CoFe2O4 (CFO) ferrimagnetic insulating films. The results can be described in terms of the recently discovered spin Hall magnetoresistance (SMR). The magnitude of the SMR depends on the interface preparation conditions, being optimal when Pt/CFO samples are prepared in situ, in a single process. The spin-mixing interface conductance, the key parameter governing SMR and other relevant spin-dependent phenomena such as spi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
124
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(138 citation statements)
references
References 41 publications
12
124
1
1
Order By: Relevance
“…Such an AMR signature has never been observed in previous studies of Pt/CFO, but it has been previously reported for other Pt/FMI systems and is accepted as the most reliable test among transport measurements for MPE [22][23][24]. We also perform the β-scan and observe SMR with similar magnitude as reported in previous studies [16][17][18]20] (Figure 3a, red curve), the remaining hysteretic signal of Pt/CFO shows higher coercivity and substantially larger remanence ratio than the out-of-plane hysteresis loop of bulk CFO (Figure 1e). These different interfacial magnetic properties might be due to the exchange interaction between the CFO and Pt moments or a surface magnetic anisotropy at the CFO/Pt interface.…”
supporting
confidence: 67%
“…Such an AMR signature has never been observed in previous studies of Pt/CFO, but it has been previously reported for other Pt/FMI systems and is accepted as the most reliable test among transport measurements for MPE [22][23][24]. We also perform the β-scan and observe SMR with similar magnitude as reported in previous studies [16][17][18]20] (Figure 3a, red curve), the remaining hysteretic signal of Pt/CFO shows higher coercivity and substantially larger remanence ratio than the out-of-plane hysteresis loop of bulk CFO (Figure 1e). These different interfacial magnetic properties might be due to the exchange interaction between the CFO and Pt moments or a surface magnetic anisotropy at the CFO/Pt interface.…”
supporting
confidence: 67%
“…One could take advantage of the spin-mixing conductance concept [5,6] at nonmagnetic metal (NM)/ferromagnetic insulator (FMI) interfaces, which governs the interaction between the spin currents present at the NM and the magnetization of the FMI. This concept is the basis of new spindependent phenomena, including spin pumping [6][7][8][9][10][11][12], spin Seebeck effect [6,13], and spin Hall magnetoresistance (SMR) [6,[14][15][16][17][18]. In these cases, a NM with large spin-orbit coupling is required to convert the involved spin currents into charge currents via the inverse spin Hall effect [19].…”
mentioning
confidence: 99%
“…In this model the "effective" mixing conductance g eff ↑↓ contains terms that quantify not only relaxation of the spin current within the NM layer g ↑↓ , but also the ability of the spin current to cross the FM-NM interface, characterized by an effective specific interface spin resistance R Ã and relaxation associated with crossing the interface, termed spin memory loss δ. Chen and Zhang very recently proposed an alternate model, based on spin memory loss due to interfacial (Rashba, in their calculations) SOI [1]. Because of interfacial spin resistance and/or spin memory loss, details of the FM-NM interface structure can have an important role in determining the damping contribution due to spin pumping [6,9]. This Letter describes the results of spin-pumping measurements using a more complex multilayered sample structure with FM (Co) sandwiched between NM layers in symmetric (Ta=Cu underlayers and Cu=Ta overlayers) and asymmetric (Ta=Cu underlayers, Ir=Ta overlayers) structures to demonstrate the role of local interface structure in spin pumping.…”
mentioning
confidence: 99%
“…A quantitative physical analysis of spin currents crossing interfaces [1][2][3] in ferromagnetic (FM) thin-film multilayers will provide a deeper fundamental understanding required for applications of such nanoscale magnetic systems in magnonics [4], spin caloritronics [5,6], and spintronics [7][8][9]. Precessional magnetization dynamics have been used extensively to access interfacial spin transport where spin current flows from magnetization precession in a FM thin film into an adjacent nonmagnetic (NM) layer.…”
mentioning
confidence: 99%